Isolated Metalloid Tellurium Atomic Cluster on Nitrogen‐Doped Carbon Nanosheet for High‐Capacity Rechargeable Lithium‐CO2 Battery. Issue 7 (16th January 2023) - Wang, Ke; Liu, Dongyu; Liu, Limin; Li, Xinyang; Wu, Hu; Sun, Zongjie; Li, Mingtao; Vasenko, Andrey S.; Ding, Shujiang; Wang, Fengmei; Xiao, Chunhui
Abstract: Rechargeable Li‐CO2 battery represents a sustainable technology by virtue of CO2 recyclability and energy storage capability. Unfortunately, the sluggish mass transport and electron transfer in bulky high‐crystalline discharge product of Li2 CO3, severely hinder its practical capacity and rechargeability. Herein, a heterostructure of isolated metalloid Te atomic cluster anchored on N‐doped carbon nanosheets is designed (TeAC @NCNS) as a metal‐free cathode for Li‐CO2 battery. X‐ray absorption spectroscopy analysis demonstrates that the abundant and dispersed Te active centers can be stabilized by C atoms in form of the covalent bond. The fabricated battery shows an unprecedented full‐discharge capacity of 28.35 mAh cm −2 at 0.05 mA cm −2 and long‐term cycle life of up to 1000 h even at a high cut‐off capacity of 1 mAh cm −2 . A series of ex situ characterizations combined with theoretical calculations demonstrate that the abundant Te atomic clusters acting as active centers can drive the electron redistribution of carbonate via forming TeO bonds, giving rise to poor‐crystalline Li2 CO3 film during the discharge process. Moreover, the efficient electron transfer between the Te centers and intermediate species is energetically beneficial for nucleation and accelerates the decomposition of Li2 CO3 on the TeAC @NCNS during the discharge/charge process. Abstract : A heterostructure of isolated metalloid Te atomic cluster anchored on N‐doped carbon nanosheet is designed as a metal‐free cathode for Li‐CO2 battery, which shows an unprecedented full‐discharge capacity of 28.35 mAh cm −2 at 0.05 mA cm −2 and long‐term cycle life of up to 1000 h even at a high cut‐off capacity of 1 mAh cm −2 .